Limbic and paralimbic structures driving ictal central apnea. (12th February 2019) - Lacuey, Nuria; Hampson, Johnson P.; Harper, Ronald M.; Miller, Jonathan P.; Lhatoo, Samden
Abstract : Objective: To precisely identify cortical regions that modulate breathing, and delineate a network of cortical structures that underpin ictal central apnea (ICA) during epileptic seizures. Methods: We electrically stimulated multiple cortical structures in patients undergoing stereotactic EEG (SEEG) evaluation before epilepsy surgery. Structures investigated were orbitofrontal cortex, anterior and posterior cingulate and subcallosal gyri, insula, hippocampus, parahippocampal gyrus, amygdala, temporo-polar cortex, antero-mesial fusiform gyrus, and lateral and basal temporal cortices. Chest/abdominal excursions using thoracic/abdominal belts, peripheral capillary oxygen saturation, end tidal and transcutaneous carbon dioxide, and airflow were continuously monitored. Results: Nineteen consecutive adult patients (10 female) aged 18–69 years were investigated. Transient central apnea was elicited in 13/19 patients with amygdala, hippocampus head and body, anterior parahippocampal gyrus, and antero-mesial fusiform gyrus. Insula, cingulate, subcallosal, orbitofrontal, lateral, and basal temporal cortices stimulation did not induce apnea. Apnea duration was associated with stimulus duration ( p < 0.001) and current intensity ( p = 0.004). Conclusions: These findings suggest a limbic/paralimbic mesial temporal breathing modulation network that includes amygdala, hippocampus, anterior parahippocampal, and antero-mesial fusiform gyri. These structures likely represent anatomical and functional substrates for ICA, a putative sudden unexpected death in epilepsy (SUDEP) breathing biomarker. Damage to such areas is known to occur in high SUDEP risk patients and SUDEP victims, and may underpin the prolonged ICA that is thought to be particularly dangerous. Furthermore, inclusive targeting of apnea-producing structures in SEEG implantations, peri-ictal breathing signal recordings, and stringent analysis of apneic sequences in seizure semiology may enhance accurate identification of symptomatogenic and seizure onset zones for epilepsy surgery.